Air Writing as a Technique for the Acquisition of Sino‐Japanese Characters by Second Language Learners. Issue 3 (22nd July 2015) - Thomas, Margaret
<x xml:space="preserve">Abstract</x> This article calls attention to a facet of the expertise of second language (L2) learners of Japanese at the intersection of language, memory, gesture, and the psycholinguistics of a logographic writing system. Previous research has shown that adult L2 learners of Japanese living in Japan (similarly to native speakers of Japanese) often spontaneously produce highly articulated movements of the fingertips or hands when learning or recalling Sino‐Japanese orthographic characters (kanji). These movements, known in Japanese as kūsho (air writing), trace out abstract representations of kanji, or parts of kanji, presumably as a kinesthetic aid to learning and recall. The current study tests that presumption with respect to learning, by comparing the accuracy with which adult L2 learners of Japanese (N = 75) memorize the shapes of complex, novel kanji under three different learning conditions. Results show that kūsho is associated with a small but statistically significant advantage in accuracy of recall, compared to either passive visual inspection or the conventional technique of memorizing the shapes of kanji by iterative paper‐and‐pen copying.